Programa Câmara Jovem: limites e possibilidades de um processo de socialização política - Thomazini, Thaís Damaris da Rocha (2012)
This research aims to understand and analyze the Câmara Jovem program, created in 2007 by the legislative power of Cascavel city, located in the Paraná State in Brazil, in a partnership with the Regional Education Center. The program allows the participation of public and private schools, represented by students of elementary and high school levels. The students which are chosen by vote among the others students are called of Youth Councilors and have to represent their school and community in the Câmara Jovem during a year. In accordance with its resolution, the program aims to integrate the young people with the policy, to promote the integration between the legislative power and public and private schools in the city, to create opportunities to young people learn the legislative function of municipal government and to contribute to the formation of citizens able to participate in the political reality. In this context, this research aims to understand the implications that the socialization political process proposed by this program may have on the political culture of the young participants. Firstly, a literature about the concept of political socialization were studied and analyzed. The authors present their analyze about the possible contributions and limits of this process in the politcal formation of adolescents and youth people, and also for the democracy. From the theoretical study and the research problem presented, it was decided to realize a case study using qualitative methodological procedures. In this procedures we can detach document analysis, field research and participant observation of sessions of the program, and semi-structured interviews with young councilors that participate or have participated in the program. In order to corroborate with the qualitative study, primary quantitative data were collected and analyzed by means of objective questionnaire applied in high school students from public and private schools in the city. The use of quantitative data aimed to prepare a comparative analysis between students who participate as young councilors and students who do not participate in the program. This action searches to understand the elements that are envolved with the youth participation in the program, and the way that this influence may contribuite in the formation of political conceptions and attitudes of young participants. The socialization political process proposed by the program, is characterized by an emphasis on learning and integration of the young with the policy, and motivated us to reflect about which conception of politics is taught to young people, and the possible implications that this process may have on the political education of young participants.